HEAT TRANSFERS AND PRESSURE DROPS IN ROTATING HELICAL PIPES - YILDIZ, C; BICER, Y; PEHLIVAN, D (Elsevier Sci Ltd, 1995)
Helical pipes are employed extensively in chemical reactors, reservoirs, nuclear generators, evaporators and condensation flow systems as well as energy saving applications. In this study, in older to increase the heat-transfer rates in helical pipes of various diameters, the rotation of the pipes was considered experimentally. An experimental set-up for determining the heat-transfer rates and pressure drops occurring, because of the centrifugal effects on the rotating helical pipes, was designed. The heat-transfer rates and pressure drops were measured for various air-flow rates and helical pipe rotational speeds. Although the rotation caused an increase in pressure drop, heat-transfer capacities of the helical pipes were observed to improve notably. The Nusselt numbers rose due to the increases in Reynold's numbers and heat inputs into the system. Beside these, further improvements in heat transfer were observed with the decreasing curvature diameter of the helical pipe.